2019
DOI: 10.1002/ange.201900061
|View full text |Cite
|
Sign up to set email alerts
|

Blinking Beats Bleaching: The Control of Superoxide Generation by Photo‐ionized Perovskite Nanocrystals

Abstract: Moisture-or oxidation-induced degradation is am ajor challenge in the advancement of perovskites-based technology.T he oxidation is caused by electron transfer from ap hoto-excited perovskite nanocrystal to oxygen and the formation of superoxide that disintegrates the perovskite structure.I na ir,t he emission intensity of am ethylammonium lead iodide (MAPbI 3 )p erovskite nanocrystal continuously decreases,whereas ananocrystal in argon or apolymer shows exceptionally stable emission intensity.Surprisingly,ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 59 publications
0
16
1
Order By: Relevance
“…To cover a broad range of frequencies, we measured PL traces as long as 75 min with 30 ms time resolution resulting in 150 000 data points covering at least one order of magnitude larger frequency range than the currently available data for MHPs. [26][27][28][29][30][31][32] One can see that PL fluctuations are very complex consisting of jumps between multiple intensity levels and semigradual undulations (Figure 1a-f and Figure S2.1 and Note S2, Supporting Information). Often the lowest PL intensity level is not close to zero.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To cover a broad range of frequencies, we measured PL traces as long as 75 min with 30 ms time resolution resulting in 150 000 data points covering at least one order of magnitude larger frequency range than the currently available data for MHPs. [26][27][28][29][30][31][32] One can see that PL fluctuations are very complex consisting of jumps between multiple intensity levels and semigradual undulations (Figure 1a-f and Figure S2.1 and Note S2, Supporting Information). Often the lowest PL intensity level is not close to zero.…”
Section: Resultsmentioning
confidence: 99%
“…[16,18] It is interesting that PL blinking of large crystals [21,24] was reported even before the same phenomenon in MHP colloidal quantum dots (QDs) was observed. [25][26][27][28][29][30][31][32][33] The nature of these fluctuations lay in the presence of strong metastable nonradiative recombination centers with a very large recombination cross section (so-called supertraps). [19,21] Thus, PL yield depends on the actual number of metastable nonradiative recombination centers per crystal which fluctuates in time and depends on other conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At room temperature, APbX 3 NCs have been shown to emit a regular stream of single photons with very high single photon purity, as evidenced by the antibunching in the second-order correlation function [ g 2 (0) < 0.1]. These NCs are presently nearly unmatched in terms of spectral tunability and facile solution synthesis and processability. However, despite their great potential, single perovskite NCs still suffer from insufficient optical stability in ambient conditions. , Moisture-assisted photodegradation is widely regarded as a major cause of instability, in addition to the thermal and solvent lability of these materials. At the single particle level, the dynamic blueshift of the PL emission and a concomitant PL quenching were indeed attributed to the photoaccelerated reaction with atmospheric water …”
mentioning
confidence: 99%
“…[48,53] Using the same techniques of single-molecule spectroscopy and time-resolved spectroscopy, the fluorescence blinking has recently been investigated in MAPbBr 3 QDs, [57][58][59][60] CsPbBr 3 QDs, [61][62][63][64] 0D Cs 4 PbBr 6 , [65] MAPbI 3 QDs. [66] Mandal et al [67] observed blinking in inorganic perovskite CsPbBr 3 QDs. As shown in Figure 2A,B, different ON/OFF power laws are confirmed for different excitation wavelengths of 405, 463, and 488 nm.…”
Section: Fluorescence Intermittency In Single Perovskite Quantum Dot mentioning
confidence: 99%